Habilidades de leitura e escrita e funções executivas em escolares nascidos a termo e pré-termo moderado - Nóro, Letícia Arruda (2022)
The development of cognitive function can be influenced by gestational, perinatal and/or postnatal complications, which, in their presence, can lead to lower cognitive levels. As examples of these factors, prematurity can be mentioned. There is evidence that moderately preterm children present alterations in several linguistic subdomains, and these alterations are variable. There is a need to investigate this relationship between prematurity and learning. Once this relationship is confirmed, it is believed that the study will provide subsidies for professionals in speech therapy, education and developmental psychology, contributing to the advancement of the student. This study aimed to analyze and compare the learning performance of children born at term and moderately preterm. This work was approved by the Ethics and Research Committee (CEP) of this educational institution, following the regulation of resolution 466/2012. The initial sample of this study consisted of 31 children aged 7 to 9 years. The following inclusion criteria were used: subjects born at term; subjects born moderately preterm (between 35 and 37 weeks); subjects duly enrolled from the 2nd to the 4th year of the researched schools, being a member of a monolingual BP-speaking family; children of both genders; present age-appropriate understanding language. Tests were performed with the phonological awareness test protocols by choice of pictures, Children's Hayling Test, balanced dictation, tests of assessment of reading processes, alternating stimulus naming, reading fluency test. The results showed a significant difference in relation to the superiority of the tests of schoolchildren born at term in the following assessments: executive functions, dictation, reading processes and phonological awareness. This suggests that moderate preterm infants can be considered a population at risk for learning disabilities that can negatively affect academic performance in the long term.